Identification of N6-Methyladenosine-Associated Long Non-coding RNAs for Immunotherapeutic Response and Prognosis in Patients With Pancreatic Cancer - Yu, Xinshuang; Dong, Peng; Yan, Yu; Liu, Fengjun; Wang, Hui; Lv, Yajuan; Song, Meijuan; Yao, Qingqiang; Hu, Sanyuan (Frontiers in Cell and Developmental Biology, 2021)
Pancreatic cancer is a highly aggressive disease with poor prognosis. N6-methyladenosine (m6A) is important in post-transcriptional modification on both messenger RNA(mRNA) and long non-coding RNA (lncRNA). However, m6A-associated lncRNAs (m6A-lncRNA)and their value in predicting clinical outcomes and immune microenvironment status in pancreatic cancer patients remain largely unexplored. This study aimed to evaluate the importance of m6A-lncRNA and established a m6A-lncRNA signature for predicting immunotherapeutic responses and prognosis of pancreatic cancer. m6A-lncRNA co-expression networks were constructed using data from TCGA and GTEx database.We constructed an 8 m6A-lncRNA signature risk model based on the least absolute shrinkage and selection operator (LASSO) analysis , and stratified patients into high- and low-risk groups with significantly different overall survival (HR = 2.68, 95 % CI = 1.74–4.14, P < 0.0001). Patients in the high-risk group showed significantly reduced OS compared to patients in the low-risk group (P < 0.001). The clinical characteristics and m6A-lncRNA signiture risk score were used to construct a nomogram which can accurately predict OS in pancreatic cancer. TIMER 2.0 were used to investigate tumor immune infiltrating cells and its relationship with pancreatic cancer .CIBERSORT analysis displyayed increased higher infiltration proportions of M0 and M2 macrophages,and lower infiltration of naive B cell, CD8+T cell and Treg cells in the high-risk group.Functional annotation using ssGSEA showed that T cell infiltration and the differential immune-related check-point genes are expressed at low level in the high-risk group (P < 0.05). In summary, our study constructed a novel m6A-associated lncRNAs signature as biomarkers for predicting immunotherapeutic responses and provided a novel nomogram for prognosis prediction of pancreatic cancer.